Antibacterial effects of Curcuma species and Vigna radiata against MRSA, MRSE, and Propionibacterium acnes - Geetha, Subramaniam; Kirthigaa, Ghandi; Lalita Ambigai, Sivasamugham (INTI International University, 2020)
Bacterial infections can be treated by antibiotics, but bacteria are developing resistance against antibiotics which has led to a global threat. Antibiotic-resistant bacteria will result in hard-to-treat infections. These will increase medical costs, lengthen hospital stays and increase in mortality rate. Many studies are searching for a promising solution for antibiotic resistant issues. In this research, three herbal plants, Curcuma aromatica, Curcuma zedoaria, and Vigna radiata were used to study the antibacterial activity against ten gram positive strains of bacteria, which were Staphylococcus aureus, Staphylococcus aureus FB408/B, Staphylococcus epidermidis, Staphylococcus epidermidis S15B/A and Propionibacterium acnes as well as three strains of Methicillin Resistant Staphylococcus aureus (MRSA), which were MRSA positive control, MRSA S16B/A, MRSA F13, and as well as two strains of Methicillin Resistant Staphylococcus epidermidis (MRSE), which were MRSE S19 and MRSE S23. These three plants were selected for this study because they are commonly using in Chinese and Indian traditional medicines as wound healing agents and bath scrubs. Phytochemicals from C. aromatica, C. zedoaria, and V. radiata were extracted with 85% ethanol using a Soxhlet extractor and concentrated using a rotary evaporator. Phytochemical screening was conducted and analyzed the presence of plant secondary metabolites that are involved in antibacterial activity. All the tested plant extracts contained terpenoids, phenols and tannins in general. These ethanolic extracts were tested against the ten gram-positive isolates. All plant extracts inhibited bacterial growth with variable potency. Synergistic effects were observed in combination of the three plants extracts when tested with S. aureus FB408/B and MRSA F13. Furthermore, when tested C. aromatica with C. zedoaria, showed a higher antimicrobial effect against the MRSA positive control in combination, than individually. The combination of C. zedoria with V. radiata on the other hand showed higher activity in P. acnes. Even though synergistic effects were observed, individual plant extract of C. aromatica and C. zedoaria have shown the greatest antibacterial activity against most of the tested isolates. The results in this study can be used to propose an effective facial product with C. aromatica extracts to inhibit activity of common skin pathogens and antibiotic resistant bacteria such as MRSA and MRSE that are found on human skin.